Pengembangan Media Papan dan Kartu Rahasia (PAKARSA) untuk Meningkatkan Hasil Belajar IPA Siswa Sekolah Dasar - Nisa, Alfiyatun; Widiyono, Aan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
This development research was carried out because there were difficulties for students to understand material changes in the shape of objects during the learning process and low student learning outcomes, this happened in the learning process applying inappropriate learning. The purpose of this study was to develop secret board and card media (PAKARSA) to improve science learning outcomes. Research on the development of secret board and card media (Secret) uses Research and Development (R&D) research with the Bord & Gall model with 8 stages. This research was conducted on 30 grade IV students at SDN 3 Kawak Jepara. Media validity is based on assessments made by material experts and media experts. Media expert validation 1 obtains 95% results, media expert validation 2 obtains 90% results, thus obtaining an average result of 92.5% % and material expert validation obtains 90% results so that it occupies the lowest learning media which is very feasible. The average pretest score was 49% with 4 students completing and the posttest average score was 80% with 25 students completing. The t-test was used to determine the effectiveness of the learning media used, the results of the t-test showed that sig (2-tailed) 0.000 <0.05 so that Ho was rejected and Ha was accepted. Based on the results of this development research, it can be interpreted that there is an increase in learning outcomes after using board media and secret cards (PAKARSA).